2012
DOI: 10.1007/s00244-012-9752-9
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Toxicity and Benthic Invertebrate Field Colonization of Upper Columbia River Sediments: Finding Adverse Effects Using Multiple Lines of Evidence

Abstract: From 1930 to 1995, the Upper Columbia River (UCR) of northeast Washington State received approximately 12 million metric tons of smelter slag and associated effluents from a large smelter facility located in Trail, British Columbia, approximately 10 km north of the United States-Canadian border. Studies conducted during the past two decades have demonstrated the presence of toxic concentrations of heavy metals in slag-based sandy sediments, including cadmium, copper, zinc, and lead in the UCR area as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…(), Fairchild et al. (), we considered relative distances in the UCR by river miles. Accordingly, our test sediments were collected between river miles 705 and 738 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(), Fairchild et al. (), we considered relative distances in the UCR by river miles. Accordingly, our test sediments were collected between river miles 705 and 738 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…() observed that cadmium, copper, lead and zinc concentrations occur in excess of biological criteria for sediments. Other studies have reported reduced survival of amphipods ( Hyallela azteca ) and reduced growth of midge ( Chironomus dilutes ) when exposed to these slag‐contaminated sediments (United States Environmental Protection Agency, ; Besser et al., ; Fairchild et al., ). Among these metals, copper appears to approach concentrations that are lethal to some species.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bortleson et al (2001) tested Upper Columbia River sediments in 1994 and documented reduced survival of the amphipod Hyalella azteca in acute (7-d) whole-sediment tests. Other recent studies have examined physical and chemical characteristics of riverine and reservoir sediments of the Upper Columbia River associated with release of dissolved metals (Paulson and Cox 2007), toxic effects in laboratory tests (Besser et al 2008), and reduced colonization of slag-and metal-rich sediments by benthic invertebrates (Fairchild et al 2012). These studies reported toxicity to both species from sediments from sites in the riverine reach near the border and the upper end of the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported toxicity to both species from sediments from sites in the riverine reach near the border and the upper end of the reservoir. Other recent studies have examined physical and chemical characteristics of riverine and reservoir sediments of the Upper Columbia River associated with release of dissolved metals (Paulson and Cox 2007), toxic effects in laboratory tests (Besser et al 2008), and reduced colonization of slag-and metal-rich sediments by benthic invertebrates (Fairchild et al 2012). All of these studies reported that toxic effects were associated with coarse-grained (sandsized) sediments of the riverine reach, which contained large amounts of metal-rich slag.…”
Section: Introductionmentioning
confidence: 99%